1986
DOI: 10.1007/bf01753416
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of autologous cells in minced and devitalized rat skeletal muscles

Abstract: Triceps surae of 3 week-old female Wistar rats were minced and orthotopically autografted. Thirty days later, the regenerates developed a force of 314 +/- 58 mN during an isometric maximal tetanus and the maximal area of the muscle tissue was 3.2 +/- 0.5 mm2 (n = 9) in a cross-section. At 60 days, their mean maximal isometric force was increased (1159 +/- 367 mN) as also were their maximal muscle cross-section area (6.8 +/- 0.7 mm2;n = 6). If the minces were devitalized by a freeze and thaw procedure, the rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Numerous studies have shown that grafted satellite cells, often expanded in culture, participate in myogenesis in both normal (Jones, 1979;Lipton and Schultz, 1979;Alameddine et al, 1989) and myopathic (Karpati, 1989;Law et al, 1990;Morgan et al, 1990;Huard et al, 1991) host muscle, but there has been little interest in the use of cell grafts to improve regeneration. In the only such study of which we are aware, Ghins et al (1986) found that although satellite cells isolated from the contralateral leg could support regeneration in devitalized mince, the cells did not enhance regeneration when added to viable mince. The cells were not purified nor expanded in culture, which may account for the lack of effect as compared with the present study.…”
Section: Augmented Mincementioning
confidence: 88%
“…Numerous studies have shown that grafted satellite cells, often expanded in culture, participate in myogenesis in both normal (Jones, 1979;Lipton and Schultz, 1979;Alameddine et al, 1989) and myopathic (Karpati, 1989;Law et al, 1990;Morgan et al, 1990;Huard et al, 1991) host muscle, but there has been little interest in the use of cell grafts to improve regeneration. In the only such study of which we are aware, Ghins et al (1986) found that although satellite cells isolated from the contralateral leg could support regeneration in devitalized mince, the cells did not enhance regeneration when added to viable mince. The cells were not purified nor expanded in culture, which may account for the lack of effect as compared with the present study.…”
Section: Augmented Mincementioning
confidence: 88%
“…Given the dearth of muscle fiber regeneration typically observed in whole and partial (i.e., VML) muscle ablation models when devitalized or acellular biological scaffolds are implanted (Ghins et al. , , ; Schultz et al. ; Corona et al.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, investigations in which minced muscle grafts were manipulated to vary the level of muscle stem cell delivery indicated a corresponding magnitude of muscle fiber regeneration (Ghins et al. , , ). Notably, when only devitalized grafts were implanted (i.e., no muscle progenitor/stem cells), no muscle fiber regeneration was observed, unless freshly isolated or cultured muscle progenitor cells were co‐delivered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations